2003
DOI: 10.3177/jnsv.49.287
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Retinol and .ALPHA.-Tocopherol Levels in Centenarians

Abstract: Recent evidence indicates that longevity may be achieved when efficient defence mechanisms against oxidative stress, infections, neoplasia, and cardiovascular events are preserved. Centenarians represent an example of "successful aging," and the aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…dl-a-tocopherol and all-trans-retinol in serum showed a correlation coefficient of 0.268 (p,0.0001), confirming the findings of other studies [134,135]. Both were also correlated with MDA, strengthening their protective role in terms of lipid peroxidation-induced damage [108,136,137].…”
supporting
confidence: 91%
“…dl-a-tocopherol and all-trans-retinol in serum showed a correlation coefficient of 0.268 (p,0.0001), confirming the findings of other studies [134,135]. Both were also correlated with MDA, strengthening their protective role in terms of lipid peroxidation-induced damage [108,136,137].…”
supporting
confidence: 91%
“…This, in turn, may promote unremitting inflammatory and/or autoimmune processes negatively correlated with human longevity (Zanni et al ., 2003). Indeed, vitamin A levels are consistently elevated in healthy centenarians, suggesting a protective role in immune system maintenance by retinoids (Mecocci et al ., 2000; Basile et al ., 2003; Franceschi and Bonafe, 2003; Polidori et al ., 2007). According to this, a large body of experimental studies have suggested several molecular mechanisms underlying the beneficial effects of retinoids in immune system disorders.…”
Section: Retinoids Act As Immunomodulatorsmentioning
confidence: 99%
“…Nutrition related factors that have been explored in centenarians include low energy intakes (3), antioxidant status (46), and cardiovascular diseases in centenarians and their offspring (710). We reported in a population-based study of centenarians that the prevalence of vitamin D deficiency was 8.9% (< 25 nmol/L 25-hydroxyvitamin D) and of vitamin D insufficiency was 36.7% (< 50 nmol/L) (2).…”
Section: Introductionmentioning
confidence: 99%